The effectiveness of low salinity waterflooding in naturally fractured reservoirs - Aljuboori, F.A. (Elsevier B.V., 2020)
Low Salinity (LoSal) waterflooding is a technique which promises to improve and enhance oil recovery. The method has been studied widely in the laboratories using various core plug samples of sandstones and carbonates. Most of the experimental outcomes have demonstrated the possibility of recovery increment in conventional reservoirs. Meanwhile, it is rare to find a discussion in these experiments about the effectiveness of LoSal waterflooding in naturally fractured reservoirs. In this paper, we investigate the potential benefits in fractured reservoirs using simulations. It is often reported from coreflood experiments that LoSal injection has the ability to alter the rock wettability and reduce residual oil saturations through chemical and physical interactions between the rock-oil-water system. Based on the published work, we have calculated relative permeability curves to represent the flow in regions flooded with LoSal water. This includes a qualitative representation of uncertainty. In this sense, the relative permeabilities are a proxy for any physical and chemical mechanisms which are not explicitly represented. The newly generated flow curves were applied to simulate LoSal waterflooding using a fine-scale model and a field scale model based on a fractured reservoir from the Middle East. The simulation results underline the benefits of LoSal whereby the oil recovery from fractured reservoirs can be increased. An additional benefit is the control of water production. The fine-scale modelling has provided an in-depth analysis and accurate estimation of the oil recovery without modelling artefacts or limitations, where an increment of (12â14) of the Stock Tank Oil Initially In Place (STOIIP) were obtained under secondary and tertiary recovery scheme, respectively. The investigated scenarios demonstrated a sensitivity to the newly generated flow curves and how they affect the ultimate oil recovery. However, for the field scale model, a higher oil production rate has maintained during LoSal waterflooding up to 32 K BPD by the end of year fourteen compared with 25 K BPD in case of high salinity scenario, besides a reduction in the produced water by 35.7. Therefore, the effectiveness of LoSal brine required a longer time frame to observe the improvements in the oil displacement or sweep efficiency. Â© 2020 Elsevier B.V.